(untitled) (Computer systems and information technologies, 2020)
Today, the efficient use of energy resources is one of the most important tasks. The fastest growing sector of energy consumption in the world is electricity, which is projected to grow by 56% by 2035, and in developed countries almost all the growth is due to the generation and consumption of electricity and heat. Further growth of energy consumption by the population is also expected. At the same time, almost a third of the total energy consumption is made up of certain losses, ie energy is consumed for other purposes. Against the background of global growth in energy consumption, the rate of further accumulation of CO2 emissions will increase. That is why the European Union, United Nations bodies, international financial organizations and the International Energy Agency give priority to energy efficiency issues. To this end, a set of mechanisms and practical tools for economic stimulation of measures to implement modern energy-saving technologies is used at the international level. Smart home is a system for managing the basic life support processes of both small systems (commercial, office premises, apartments, cottages) and large automated complexes (commercial and industrial complexes). One of the important tasks to be solved by the concept of a modern smart home is the problem of energy efficiency and energy saving. Effective control of heating, ventilation, air conditioning, more efficient use of traditional appliances and the introduction of energy-efficient equipment in the building are important to ensure productive, healthy and safe work and life of residents, play an important role in preventing energy loss and reduce impact on the environment. In addition, improving the efficiency of energy management is the only approach to ensuring the energy efficiency and energy saving of many existing buildings that cannot be upgraded according to the requirements of modern construction technologies. The paper presents an overview of modern methods and technologies aimed at ensuring energy efficiency and energy saving in the smart home system.